2019
DOI: 10.18332/tid/111539
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a smoking cessation intervention at follow-up after 5 years among tuberculosis patients in China

Abstract: INTRODUCTIONSmoking cessation should be part of tuberculosis (TB) treatment, but a cessation service is not available as part of a routine TB service in most low- and middle-income countries. WHO and The International Union Against Tuberculosis and Lung Disease (The Union) issued a guideline and China implemented a pilot project 5 years ago. This study aimed to determine changes in smoking status among TB patients at 5 years after completion of anti-TB treatment to observe long-term outcome of a smoking cessat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
11
0
2
Order By: Relevance
“…Merokok juga merupakan faktor risiko penundaan dalam mengakses pelayanan kesehatan pada pasien TB (Lin et al, 2019). Kebiasaan merokok dapat merusak paru-paru dan menurunkan kekebalan tubuh yang mempengaruhi respon penderita terhadap pengobatan TB (Tachfouti et al, 2011).…”
Section: Pendahuluanunclassified
“…Merokok juga merupakan faktor risiko penundaan dalam mengakses pelayanan kesehatan pada pasien TB (Lin et al, 2019). Kebiasaan merokok dapat merusak paru-paru dan menurunkan kekebalan tubuh yang mempengaruhi respon penderita terhadap pengobatan TB (Tachfouti et al, 2011).…”
Section: Pendahuluanunclassified
“…This teachable moment should be utilized. Offering smoking cessation within a population willing to quit smoking has been shown to achieve high quit rates 39 . By integrating smoking cessation within TB care, patients can be supported to quit at this opportune moment.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Therefore, initiating tobacco cessation intervention during DOTS will bene t TB patients in terms of their treatment outcome and improve their adherence to TB treatment. A prospective cohort in Hong Kong also found that 49.6% of smokers who quit will remain nonsmoking 5 years after the cessation intervention while receiving TB treatment (44). This nding supports the longterm effect of the TB smoking cessation intervention delivered by TB chest clinics in reducing smoking prevalence among TB patients who smoke.…”
Section: Characteristics Of Tb Patients Who Smokementioning
confidence: 58%